Analisis Kritik Kamil Musthafa Al-Siba’i terhadap Kitab Fajr Al-Islam Karya Ahmad Amin - Normala Rista Wike Umami (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2025)
This study discusses how Kamil Musthafa al-Siba’i criticizes Ahmad Amin's book Fajr al-Islam, particularly regarding Amin's views on the emergence of fabricated hadiths and the prohibition of writing hadiths during the Prophet's time. In general, this study aims to explain the differences in perspective between the two figures, as well as to assess the basis of the arguments used by each. The method employed is a literature review by examining the book Fajr al-Islam, al-Siba’i's writings, and other supporting literature. The analysis is conducted by comparing Amin's more textual opinions with al-Siba’i's explanations, which are more contextual and historical. The results of the study show that al-Siba’i considers some of Amin's understandings of hadith to be inaccurate, especially when Amin concludes that the fabrication of hadiths had already occurred during the Prophet's time and when he interprets the prohibition of writing hadiths in an absolute manner. Al-Siba’i emphasized that the prohibition was temporary and aimed at preventing confusion in the writing of the Qur’anic revelation. Al-Siba’i’s critique shows that understanding hadith requires a more comprehensive approach, taking into account the social and historical context, not just the text alone. This study highlights the importance of critical analysis in examining the works of modern Muslim thinkers to ensure an accurate and balanced understanding of Islamic sources.